Size-dependent and real-time effect of SiO2 nanoparticles on a single living HeLa Cell's membrane permeability. Issue 7 (23rd January 2015) - Kong, Weiqian; Li, Hao; Liu, Juan; SijieGuo; Han, Yuzhi; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : Low toxic and biocompatible SiO2 NPs of different sizes show different effects on cell membrane permeability. Abstract : In this study, we provide the quantitative data on the membrane permeability of a HeLa cell in the presence of different sizes of SiO2 nanoparticles (NPs, 50, 100 and 200 nm). SiO2 NPs have low cytotoxicity, but 50 and 100 nm SiO2 NPs can increase the cell membrane permeability (a reversible effect) by 12.5% (0.02 mg mL −1, 4 min) and 9% (0.02 mg mL −1, 6 min), respectively. However, the 200 nm SiO2 NPs cannot affect the cell membrane permeability.